(untitled) (Research, Society and Development, 2024)
Lactuca sativa is the most commonly used vegetable in human diets, primarily consumed in salads.The consumption of Lactuca sativa may pose risks to human health due to the likelihood of transmission of intestinal parasites. However, the hygienic and sanitary conditions of leafy greens, such as lettuce from restaurants, have been little studied. Thus, the aim of this study was to investigate parasitic contamination in lettuce from self-service restaurants randomly located on streets and in shopping centers in the municipality of Maringá, Paraná. The research conducted was a cross-sectional descriptive quantitative study, carried out between April and May 2024. A total of 44 samples were analyzed, and the positivity rate was 34.09%. Parasitological contamination was higher in samples from street restaurants, with 10 contaminated samples (22.72%), compared to the percentage found in lettuce from shopping center restaurants, with 5 contaminated samples (11.36%). In street restaurants, 18.18% of the samples showed Endolimax nana and 9.09% Giardia lamblia. In shopping center restaurants, E. nana was found in 11.36% of the samples. The presence of protozoan cysts in lettuce indicates that contamination of humans through the consumption of the vegetable is possible. To prevent such infections, hygiene measures for food handlers should be implemented.